Effect of potassium fertilizer on the nutrition and physical quality of Job’s tears (Coix lacryma-jobi L.) seeds - Haysa, Qinthara Nail; Yuwariah, Yuyun; Wicaksono, Fiky Yulianto (Universitas Padjadjaran, 2025)
Job's tears is a cereal crop that has beneficial nutrients. Potassium is known to affect the growth and yield of cereal crops, but there has been limited study on whether potassium affects the nutrition and physical quality of Job’s tears seeds. This study aimed to analyze the effect of K fertilizer on the nutritional content and physical quality of Job's tears seeds. This research was conducted from January to May 2024 at Ciparanje Experimental Field, Faculty of Agriculture, Universitas Padjadjaran, Sumedang, Indonesia. This experiment used the Randomized Block Design (RBD) method with six treatments and four replications. Various doses of K fertilizer (KCl) were tested, i.e., 0, 62.5, 125, 250, 375, and 500 kg/ha KCl. The measured nutritional content was the extraction rates of carbohydrate, protein, lipid, calcium, and potassium, while the physical quality was represented by the weight of husked grain, size of seeds, and seed hardness. Results showed that potassium increased the extraction rates of carbohydrate, protein, lipid, calcium, and potassium. Potassium also increased the weight of husked grain and size of seeds. A dosage of 500 kg/ha KCl resulted in the best nutrition, weight of husked grain, and size of seeds.